Genomic Sequence Analysis of the Mouse Naip Gene Array - Endrizzi, Matthew G.; Hadinoto, Vey; Growney, Joseph D.; Miller, Webb; Dietrich, William F. (Genome Research, 2000)
A mouse locus called Lgn1 determines differences in macrophage permissiveness for the intracellular replication ofLegionella pneumophila. The only regional candidate genes for this phenotype difference lie within a cluster of closely linked paralogs of the Neuronal Apoptosis Inhibitory Protein (Naip) gene. Previous genetic and physical mapping of the Lgn1phenotype narrowed it to an interval containing only Naip2and Naip5, suggesting that there is not complete functional overlap among the mouse Naip loci. In order to gather more information about polymorphisms among the Naipgenes of the 129 mouse haplotype, we have determined the genomic sequence of a substantial portion of the 129 Naip gene array. We have constructed an evolutionary model for the expansion of theNaip gene array from a single progenitor Naip gene. This model predicts the presence of two distinct families ofNaip paralogs: Naip1/2/3 and Naip4/5/6/7. Unlike the divergences among all the other Naip paralogs, the splits among Naip4, Naip5, Naip6, andNaip7 occurred relatively recently. The high degree of sequence conservation within the Naip4/5/6/7 family increases the likelihood of functional overlap among these genes.[The sequence data described in this paper have been submitted to the GenBank data library under accession nos. AF242431-AF242435.]
10.1101/gr.10.8.1095